Recessive Mutations in KIF12 Cause High Gamma‐Glutamyltransferase Cholestasis. Issue 4 (13th February 2019) - Ünlüsoy Aksu, Aysel; Das, Subhash K.; Nelson‐Williams, Carol; Jain, Dhanpat; Özbay Hoşnut, Ferda; Evirgen Şahin, Gülseren; Lifton, Richard P.; Vilarinho, Silvia
Abstract : Undiagnosed liver disease remains an unmet medical need in pediatric hepatology, including children with high gamma‐glutamyltransferase (GGT) cholestasis. Here, we report whole‐exome sequencing of germline DNA from 2 unrelated children, both offspring of consanguineous union, with neonatal cholestasis and high GGT of unclear etiology. Both children had a rare homozygous damaging mutation (p.Arg219* and p.Val204Met) in kinesin family member 12 ( KIF12 ). Furthermore, an older sibling of the child homozygous for p.Val204Met missense mutation, who was also found to have cholestasis, had the same homozygous mutation, thus identifying the cause of the underlying liver disease. Conclusion : Our findings implicate rare homozygous mutations in KIF12 in the pathogenesis of cholestatic liver disease with high GGT in 3 previously undiagnosed children. Abstract : Undiagnosed liver disease remains an unmet medical need in pediatric hepatology, including children high gamma‐glutamyltransferase (GGT) cholestasis. Here, we studied 3 children from 2 unrelated consanguineous families with high GGT cholestasis of unclear etiology and found that their underlying liver disease is due to recessive mutations in KIF12, which encodes kinesis family member 12.